2021
DOI: 10.30834/kjp.34.1.2021.249
|View full text |Cite
|
Sign up to set email alerts
|

Stevens-Johnson Syndrome while on lamotrigine and NSAID:A case report

Abstract: Stevens-Johnson syndrome is a severe immune-mediated cutaneous reaction occurring due to exposure to certain drugs. Lamotrigine is an FDA approved drug used in the treatment of bipolar depression. When it is given concomitantly with sodium valproate, the risk of developing Stevens-Johnson syndrome increases. Here we present the report of a patient with bipolar depression who developed serious skin rashes while on lamotrigine and NSAID prescribed by a local doctor, who recovered after timely management. This ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Various studies have shown phenytoin, carbamazepine, and lamotrigine to be the most common anticonvulsants causing SJS-TEN. 2 OXC, a 10-keto derivative of CBZ, is thought to be safer due to its distinct metabolism. 3 Oxcarbazepine is metabolized to its active metabolite, monohydroxy derivative (MHD) in contrast to carbamazepine which is readily metabolized to an epoxide metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown phenytoin, carbamazepine, and lamotrigine to be the most common anticonvulsants causing SJS-TEN. 2 OXC, a 10-keto derivative of CBZ, is thought to be safer due to its distinct metabolism. 3 Oxcarbazepine is metabolized to its active metabolite, monohydroxy derivative (MHD) in contrast to carbamazepine which is readily metabolized to an epoxide metabolite.…”
Section: Introductionmentioning
confidence: 99%